An epidemiological approach to study fatigue in the working population: the Maastricht Cohort Study - Kant, I. (BMJ Group, 2003)
In 1998, a large scale prospective cohort study of prolonged fatigue in the working population was started in the Netherlands. The ultimate goal of this Maastricht Cohort Study was to identify risk factors involved in the aetiology and natural course of prolonged fatigue in the working population and to develop preventive measures and treatments that can be used in occupational health settings. In this paper, a conceptual model for epidemiological research on prolonged fatigue is presented. This model is the basis for the Maastricht Cohort Study. Alongside the model and design, the characteristics of the study population, the prevalence and one year cumulative incidence of prolonged fatigue, as well as its relation with secondary health outcomes (psychological distress, need for recovery, and burnout) are presented. Furthermore, model, design, and the presented results are discussed.